Predictors and prognostic implications of hospital-acquired pneumonia in patients admitted for acute heart failure - Polovina, Marija; Tomić, Milenko; Viduljević, Mihajlo; Zlatić, Nataša; Stojićević, Andrea; Civrić, Danka; Milošević, Aleksandra; Krljanac, Gordana; Lasica, Ratko; Ašanin, Milika (Frontiers in Cardiovascular Medicine, 2023)
BACKGROUND: Data on predictors and prognosis of hospital acquired pneumonia (HAP) in patients admitted for acute heart failure (AHF) to intensive care units (ICU) are scarce. Better knowledge of these factors may inform management strategies. This study aimed to assess the incidence and predictors of HAP and its impact on management and outcomes in patients hospitalised for AHF in the ICU.METHODS: this was a retrospective single-centre observational study. Patient-level and outcome data were collected from an anonymized registry-based dataset. Primary outcome was in-hospital all-cause mortality and secondary outcomes included length of stay (LOS), requirement for inotropic/ventilatory support, and prescription patterns of heart failure (HF) drug classes at discharge.Of 638 patients with AHF (mean age, 71.6±12.7 years, 61.9% male), HAP occurred in 137 (21.5%). In multivariable analysis, HAP was predicted by de novo AHF, higher NT proB-type natriuretic peptide levels, pleural effusion on chest X-ray, mitral regurgitation, and a history of stroke, diabetes, and chronic kidney disease. Patients with HAP had a longer LOS, and a greater likelihood of requiring inotropes (adjusted odds ratio, OR, 2.31, 95% confidence interval, CI, 2.16-2.81; p<0.001) or ventilatory support (adjusted OR 2.11, 95%CI, 1.76-2.79, p<0.001). After adjusting for age, sex and clinical covariates, all-cause in-hospital mortality was significantly higher in patients with HAP (hazard ratio, 2.10; 95%CI, 1.71-2.84; p<0.001). Patients recovering from HAP were less likely to receive HF medications at discharge.HAP is frequent in AHF patients in the ICU setting and more prevalent in individuals with de novo AHF, mitral regurgitation, higher burden of comorbidities, and more severe congestion. HAP confers a greater risk of complications and in-hospital mortality, and a lower likelihood of receiving evidence-based HF medications at discharge.